FMRP Modulates Neural Differentiation through m(6)A-Dependent mRNA Nuclear Export - Edens, Brittany M. (Cell Rep, 2019)
N(6)-methyladenosine (m(6)A) modification of mRNA is emerging as a vital mechanism regulating RNA function. Here, we show that fragile X mental retardation protein (FMRP) reads m(6)A to promote nuclear export of methylated mRNA targets during neural differentiation. Fmr1 knockout (KO) mice show delayed neural progenitor cell cycle progression and extended maintenance of proliferating neural progenitors into postnatal stages, phenocopying methyltransferase Mettl14 conditional KO (cKO) mice that have no m(6)A modification. RNA-seq and m(6)A-seq reveal that both Mettl14cKO and Fmr1KO lead to the nuclear retention of m(6)A-modified FMRP target mRNAs regulating neural differentiation, indicating that both m(6)A and FMRP are required for the nuclear export of methylated target mRNAs. FMRP preferentially binds m(6)A-modified RNAs to facilitate their nuclear export through CRM1. The nuclear retention defect can be mitigated by wild-type but not nuclear export-deficient FMRP, establishing a critical role for FMRP in mediating m(6)A-dependent mRNA nuclear export during neural differentiation.